The significance of the raw factor in the formation of the regional international system of the Black Sea-Caspian region - A.-Ch. Ya. Abkairov (Современная наука и инновации)
The article is devoted to the importance of the raw material factor in the formation of the regional international system of the Black Sea-Caspian region. The Black Sea-Caspian region in many historical times was a zone of increased geopolitical interest of many countries. For more than a decade, the modern world has felt a contradiction in the views on the position regarding problems in this region, which is primarily due to conflict situations that are determined by the problems of the international legal status of the Black Sea-Caspian region. This is due to the use of sea routes, production and transportation, logistics for the movement of hydrocarbon resources, environmental issues, as well as the problems of escalating geopolitical tensions in this region.